G.I. Chelpanov – Founder of the First Psychological School in Russia - Zhdan, A.N. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The article is devoted to an analytical review of the work of the Russian philosopher, psychologist and teacher Georgy Ivanovich Chelpanov and his scientific school. The article describes his educational, organizational, research and pedagogical activities in pre-revolutionary and Soviet Russia. Chelpanov created a system of higher psychological education, was the author of textbooks and scientific papers, defended the need for the development of psychology as an independent science based on a subject oriented methodology on theoretical and experimental basis. The Institute of Psychology at Moscow University became the place of formation of the first scientific psychological school in Russia. Its main idea is : psychology is an independent science with its own subject, research methods and areas of application in various fields of social practice. Chelpanov created the profession of a psychologist in demand in modern society, the process continues in the activities of his students and followers, the creators of new psychological schools. Статья посвящена аналитическому рассмотрению творчества русского философа, психолога и педагога Георгия Ивановича Челпанова и его школы. Представлены сведения о его образовании, организаторской, исследовательской и педагогической деятельности в дореволюционной и советской России. Челпанов создал систему высшего психологического образования, был автором учебников и научных трудов, отстаивал необходимость развития психологии как самостоятельной науки, опирающейся на свою методологию, вооруженную адекватными ее предмету теоретическими и экспериментальными методами. Построенный по его проекту Психологический институт при Московском университете стал местом формирования первой научной психологической школы в России, главные особенности которой заключаются в следующем: психология - это самостоятельная наука, имеющая свой предмет, методы исследования и области приложения в различных сферах социальной практики. Он создал востребованную в современном обществе профессию психолога, развитие которой продолжается в деятельности его учеников и последователей, творцов новых психологических школ.